EFEKTIVITAS EKSTRAK DAUN PEPAYA DALAM PENGENDALIAN KUTU DAUN PADA FASE VEGETATIF TANAMAN TERUNG - Riski Ramadhona; Djamilah Djamilah; Mukhtasar Mukhtasar (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2018)
[EFFICACY OF PAPAYA LEAF EXTRACT IN CONTROLLING COTTON APHID DURING VEGEATIVE GROWTH STAGE OF EGGPLANT].  Cotton aphid (Aphis gossypii Glover) can cause serious economic losses in the eggplant production.  The application of synthetic pesticides can be effective in controlling the pest but it may not be the best solution for the human health and environment. Botanical pesticides have long been known for their potential as the alternative to synthetic pesticides for crop protection with reduced risk to human health and environmental hazard. Objective of this study was to compare the efficacy of papaya leaf extract solutions in controlling cotton aphid and their effect on the vegetative growth of eggplant. Papaya leaf extract solutions differing in concentration (0%, 10%, 20%, 30%, 40%, and 50%) were sprayed onto aphid infested eggplants to observe the insect mortality, crop damage, and the lethal concentration at LC50 and LC90. The mortality of aphid was significantly increased following the application of papaya leaf extract, with the highest mortality (91.33%) was found on the concentration of 50%. The lethal concentrations of the extract causing 50% (LC50) and 90% (LC90) aphid mortality were   9.98% and 41.99%, respectively. As compared to the control treatment, the crop damage was significantly reduced by the application of the papaya leaf extract solution.